Bis-indolic compounds as potential new therapeutic alternatives for tularaemia - CASPAR, Yvan; SUTERA, Vivien; BOISSET, Sandrine; DENIS, Jean-Noël; MAURIN, Max (Frontiers in Cellular and Infection Microbiology, 2014)
Francisella tularensis is the etiological agent of tularaemia and a CDC class A biological threat agent. Few antibiotic classes are currently useful in treating tularaemia, including the aminoglycosides gentamicin and streptomycin, fluoroquinolones, and tetracyclines. However, treatment failures and relapses remain frequent and F. tularensis strains resistant to antibiotics have been easily selected in vitro. In this study, we evaluated the activity of new synthetic bis-indole derivatives against this pathogen. Minimum inhibitory concentrations (MICs) of four compounds (dcm01 to dcm04) were determined for the reference strains F. tularensis subsp. holarctica LVS NCTC10857, F. tularensis subsp. novicida CIP56.12 and F. philomiragia ATCC25015, and for 41 clinical strains of F. tularensis subsp. holarctica isolated in France. Minimal bactericidal concentrations (MBCs) were determined for the dcm02 and dcm04 compounds for the LVS and two clinical strains. Killing curves were also determined for the same three strains exposed to dcm04. All tested bis-indole compounds were bacteriostatic against F. tularensis subsp. holarctica strains, with a MIC90 of 8 μg/mL for dcm01, dcm02, and dcm03, and 2 μg/mL for dcm04. Only one strain was resistant to both dcm01 and dcm03, with MICs > 32 μg/mL. In contrast, F. tularensis subsp. novicida was resistant to all derivatives and F. philomiragia was only susceptible to dcm02 and dcm04, with MICs of 16 and 4 μg/mL, respectively. MBC and killing curve experiments revealed significant bactericidal activity (i.e., 3-log reduction of the bacterial inoculum) of the dcm02 and dcm04 compounds only for the LVS strain. In conclusion, we have identified novel synthetic bis-indole compounds that are active against F. tularensis subsp. holarctica. They may be drug candidates for the development of new therapeutic alternatives for tularaemia treatment. Their further characterization is needed, especially identification of their bacterial targets.